2013
DOI: 10.1016/j.kjms.2012.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial comparing rabeprazole‐ versus lansoprazole‐based Helicobacter pylori eradication regimens

Abstract: Different types of proton pump inhibitor (PPI)-based triple therapies could result in different Helicobacter pylori eradication rates. This study aimed to compare the efficacy and safety of rabeprazole- and lansoprazole-based triple therapies in primary treatment of H. pylori infection. From September 2005 to July 2008, 426 H. pylori-infected patients were randomly assigned to receive a 7-day eradication therapy with either rabeprazole 20mgbid (RAC group, n=222) or lansoprazole 30mgbid (LAC group, n=228) in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…[22][23][24][25][26][27] Although the 14-day stand triple therapy and 7-day standard triple therapy were the leading two most commonly used regimens of Taiwanese gastroenterologists, the pooled intention-to-treat eradication rates of the two regimens were only 84.6% (804/950) and 81.0% (949/1171), respectively. 17,[21][22][23][24][25][31][32][33] This confirmed that both 14-day standard triple therapy and 7-day standard triple therapy cannot achieve an eradication rate ≥90% in Taiwan, and do not meet the recommendations of most national or international consensuses. [28][29][30] In the Maastricht V/Florence Consensus Report 28 and the Taiwan H. pylori Consensus Report, 30 bismuth quadruple therapy and nonbismuth quadruple therapy are recommended first-line therapies for H. pylori infection in areas with high clarithromycin resistance (resistance rate ≥15%).…”
Section: H Pylori Therapy Ofmentioning
confidence: 72%
See 1 more Smart Citation
“…[22][23][24][25][26][27] Although the 14-day stand triple therapy and 7-day standard triple therapy were the leading two most commonly used regimens of Taiwanese gastroenterologists, the pooled intention-to-treat eradication rates of the two regimens were only 84.6% (804/950) and 81.0% (949/1171), respectively. 17,[21][22][23][24][25][31][32][33] This confirmed that both 14-day standard triple therapy and 7-day standard triple therapy cannot achieve an eradication rate ≥90% in Taiwan, and do not meet the recommendations of most national or international consensuses. [28][29][30] In the Maastricht V/Florence Consensus Report 28 and the Taiwan H. pylori Consensus Report, 30 bismuth quadruple therapy and nonbismuth quadruple therapy are recommended first-line therapies for H. pylori infection in areas with high clarithromycin resistance (resistance rate ≥15%).…”
Section: H Pylori Therapy Ofmentioning
confidence: 72%
“…Although the 14‐day stand triple therapy and 7‐day standard triple therapy were the leading two most commonly used regimens of Taiwanese gastroenterologists, the pooled intention‐to‐treat eradication rates of the two regimens were only 84.6% (804/950) and 81.0% (949/1171), respectively 17,21–25,31–33 . This confirmed that both 14‐day standard triple therapy and 7‐day standard triple therapy cannot achieve an eradication rate ≥90% in Taiwan, and do not meet the recommendations of most national or international consensuses 28–30 …”
Section: Discussionmentioning
confidence: 96%
“…). Finally, 26 clinical trials were eligible for analysis . In Taiwan, the 7‐day standard triple therapy was the most preferred first‐line therapy for H. pylori infection (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Bantalan absorben dilapiskan pada sisi plat yang lain. Zona uji dan kontrol dari membran nitroselulosa dilapisi berturut-turut dengan 0,25 µL konjugat OTA-OVA (0,1 mg/mL) dan 0,5 µL antibodi IgY (0,1 mg/mL) (modifikasi Liu et al, 2013).…”
Section: Penyiapan Strip Imunokromatografikunclassified